Antinociceptive and Antioxidant Activity of an Aqueous Root Bark Extract of Daniellia oliveri (Rolfe) Hutch. & Dalziel (Fam: Leguminosae [Fabaceae]) in ICR Mice - Alex Boye, Patrick Amoateng, George Asumeng Koffuor, Victor Yao Atsu Barku, Eric Mishio Bawa, Odamen Enoch Anto (Journal of Applied Pharmaceutical Science, 2013)
Daniellia oliveri stem bark is used traditionally by the people of Northern Ghana to manage pain. This study therefore sought to validate the antinociceptive property of an aqueous stem bark extract of Daniellia oliveri (DOE) using murine hot plate and paw pressure pain models as well as its antioxidant property. Groups of ICR mice were pre-treated with DOE (250, 500, 1000 or 2000 mg kg-1, p.o), morphine (3 mg kg-1 , i.p), diclofenac (3 mg kg-1 , i.p) or normal saline (2 ml/kg) respectively for 0.5 - 1 h, prior to pain induction. Pain latency period were measured at 0.5 h intervals for 1.5 h. To establish the possible mode of analgesic activity, nociceptive activity of DOE was antagonized by naloxone (2 mg kg-1), glibenclamide (8mg kg-1), and theophylline (5mg kg1). The extract was screened for antioxidant property by its effect on DPPH radical scavenging activity. DOE in both pain models produced significant (P ≤ 0.001) dose and time - dependent antinociceptive effect comparable to morphine, and diclofenac. The antinociceptive effect of DOE was significantly (P ≤ 0.001) attenuated by naloxone, glibenclamide, and theophylline. DOE caused a concentration dependent percentage increase in DPPH radical scavenging activity. The aqueous stem bark extract of Daniellia oliveri therefore has antinociceptive and antioxidant effect with antinoception possibly mediated through activation of ATP-sensitive potassium channels, as well as opioidergic and adenosinergic receptor pathways.
Keywords: Nociceptive withdrawal threshold, Pain latency period, Opioidergic receptor, ATP-sensitive potassium channels.